Bioabsorbable Suture Anchor Migration to the Acromioclavicular Joint: How Far Can These Implants Go? - Giovanna Medina; Guilherme Garofo; Caio O. D’Elia; Alexandre C. Bitar; Wagner Castropil; Breno Schor (Case Reports in Orthopedics)
Few complications regarding the use of bioabsorbable suture anchors in the shoulder have been reported. What motivated this case report was the unusual location of the anchor, found in the acromioclavicular joint which, to our knowledge, has never been reported so far. A 53-year old male with previous rotator cuff (RC) repair using bioabsorbable suture anchors presented with pain and weakness after 2 years of surgery. A suspicion of retear of the RC led to request of a magnetic resonance image, in which the implant was found located in the acromioclavicular joint. The complications reported with the use of metallic implants around the shoulder led to the development of bioabsorbable anchors. Advantages are their absorption over time, minimizing the risk of migration or interference with revision surgery, less artifacts with magnetic resonance imaging, and tendon-to-bone repair strength similar to metallic anchors. Since the use of bioabsorbable suture anchors is increasing, it is important to know the possible complications associated with these devices.